2020
DOI: 10.14693/jdi.v27i3.1139
|View full text |Cite
|
Sign up to set email alerts
|

Complete Edentulism of Dental Patients in Northeastern Turkey: Prevalence and Radiographic Findings on Panoramic Radiographs Prevalence and Radiographic Findings on Panoramic Radiographs

Abstract: The prevalence of complete edentulism varies from country to country and from one region to another. Previous studies have reported the high prevalence of significant radiographic findings in edentulous patients. Objectives: This study aimed to determine the prevalence of complete edentulism retrospectively and to evaluate the frequency and location of significant radiographic findings on panoramic radiographs in edentulous jaws of dental patients in northeastern Turkey. Methods: The digital panoramic images o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Furthermore, other studies include stylohyoid ligament calcification, maxillary sinus abnormalities, and location of the mental foramen and mandibular canal. This relates to whether or not the intervention will be planned before making dentures.. 2,3,18,8 Some of radiation dose controversies regarding the use of radiography as a routine examination performed prior to denture fabrication have been discussed in several studies. Given the concerns about the accumulated effects of radiological exposure, some observers consider the need for selection regarding the use of panoramic radiographs for examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, other studies include stylohyoid ligament calcification, maxillary sinus abnormalities, and location of the mental foramen and mandibular canal. This relates to whether or not the intervention will be planned before making dentures.. 2,3,18,8 Some of radiation dose controversies regarding the use of radiography as a routine examination performed prior to denture fabrication have been discussed in several studies. Given the concerns about the accumulated effects of radiological exposure, some observers consider the need for selection regarding the use of panoramic radiographs for examination.…”
Section: Discussionmentioning
confidence: 99%
“…In the Radiographic Selection Criteria and Guidelines issued by the ADA, radiographic examination based on clinical signs and symptoms is recommended in adult patients who have recently lost teeth. 8 In addition, the Food and Drug Administration, Center for Device and Radiological Health recommends evaluation of panoramic radiographs as a support for intra-oral examination. 5 Patients who are recommended for any type of radiological examination should consider the ALARA principle (As Low As Reasonably Achievable).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have indicated a strong association between sex and age of patients with edentulism [17,28] and showed that the prevalence of total edentulism is higher in female patients, with a greater impact on their oral health and quality of life than that in male patients [4,13,17,28]. Conversely, the prevalence of total edentulism in this study was marginally higher in men (4.2%) than in women (4.1%), similar to the results of studies conducted elsewhere in Saudi Arabia [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it affects both oral and general health [1,[7][8][9][10]. Although the prevalence of total edentulism has decreased over the last decade, data from the World Health Organization (WHO) and independent studies in 42 countries show that the prevalence of total edentulism is the lowest in Nigeria (1.3%) and the highest in Bosnia-Herzegovina (78%) among those aged >65 years [1,4,5,[11][12][13][14][15]. Few studies have examined the prevalence of total edentulism in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%